Clinical and Computerized Volumetric Analysis of Posterior Fossa Decompression for Space-Occupying Cerebellar Infarction - Goulin Lippi Fernandes, Eric; Ridwan, Sami; Greeve, Isabell; Schäbitz, Wolf-Rüdiger; Grote, Alexander; Simon, Matthias (Frontiers in Neurology, 2022)
Background and Purpose: Surgical decompression of the posterior fossa is often performed in cases with a space-occupying cerebellar infarction in order to prevent coma and death. In the present study we have analyzed our institutional experience with this condition. We specifically attempted to address timing issues and investigated the role of a cerebellar necrosectomy using imaging data and volumetric analyses. Methods: We retrospectively studied pertinent clinical and imaging data including computerized volumetric analyses (preoperative/postoperative infarction volume, necrosectomy volume, posterior fossa volume) from all 49 patients undergoing posterior fossa decompression surgery for cerebellar infarction in our department from January 2012 – January 2021. Results: 35 (71%) patients had a GCS 14-15 at admission vs. only 14 (29%) before vs. 41 (84%) following surgery. Seven (14%) patients had preventive surgery (initial GCS 14-15, preoperative GCS change ≤1). Only 18 (37%) patients had mRS 0-3 scores at discharge. Estimated overall survival was 70.5% at one year. Interestingly, 18/20 (90%) surviving cases had a mRS 0-3 outcome (mRS 0-2: 12/20 [60%]) one year after surgery. Surgical timing including preventive surgery and the mass effect of the infarct within the posterior fossa assessed semi-quantitatively (Kirollos grade) and by volumetric parameters were not predictive of the patients’ (functional) outcomes. Conclusion: Posterior fossa decompression for cerebellar infarction is a life-saving procedure, but rapid recovery of the GCS after surgery does not necessarily translate into a good functional outcome. Many patients die during follow-up, but longterm mRS 4-5 outcomes are rare. Surgery should probably aim primarily at pressure relief, and the impact of removing infarcted tissue may be limited. It is probably relatively safe to initially withhold surgery in cases with a GCS 14-15.